No peace without prayer : encouraging Muslims and Christians to pray together : a Benedictine approach - Wright, Timothy, OSB. (2013)
"Abbot Timothy Wright proposes sowing a small seed from which might grow a greater respect between the world's two largest religions, Christianity and Islam. Indeed, he believes that the seed has been already planted. Christians give unique value to their revealed Scriptures as the 'Word of God'. Muslims speak of the Qur'an as God speaking to them. In No Peace without Prayer, Wright presents the case to establish groups of Christians and Muslims dedicated to sharing their respective Divine Word in ways that enhance the "other" to gain a greater mutual understanding. The key word, says Wright, is partnership, arising from their shared belief in the One God, creator of the universe, communicating with the human world and merciful to the repentant."--Back cover.
The path to dialogue: why walk it? -- Finding a way through disputed issues: will they do it? -- Defining the dialogue of spirituality: can they do it? -- The higher forms of spiritual experience compared: how far can they get? -- God's revelation and the human response: examples for inspired Scriptures -- Experience and support for a community in a dialogue of spirituality: do they encourage a decision to go ahead? -- Seeking inspiration and encouragement: can anyone inspire?
Includes bibliographical references (pages 329-336) and index.
Keywords: Christianity and other religions -- Islam; Islam -- Relations -- Christianity